Data-limited stock assessment of red mullet (Mullus barbatus) from the Iskenderun Bay, the north-eastern Mediterranean Sea - Turan, Cemal (Journal of Fisheries, 2022)
Stock size and status of red mullet Mullus barbatus were assessed via virtual population analysis and yield prediction analysis using on-board observed length-frequency catch data from the north-eastern Mediterranean Sea. The von Bertalanffy growth parameters obtained were L∞ = 35.4 cm, k = 0.42, t0 = 0.64, tanc = 0.59 and Φ′ = 2.72. Trawl-type selectivity ogive was calculated as 1.57 years corresponding to 17.1 cm TL. The virtual population analysis of M. barbatus indicated that the minimum and maximum fishing mortalities were 0.01 yr–1 and 11.1 yr–1 for the mid-length groups for 8.5 cm and 21.5 cm respectively. The estimated lowest mean biomass and yield were 3.541 t and 31 t at length 8.5, and the highest mean biomass and yield were 13.880 t at length 22.5 cm and 46.086 t at length 21.5 cm respectively. Biological reference points were FMSY = 5.85, F0.5 = 2.3, EMSY = 0.89, E0.5 = 0.77. The values for the current fishing mortality coefficient (Fcur) and the current exploitation rate (Ecur) calculated were 5.3 and 0.89 respectively. The present biological reference points indicate that the stock of M. barbatus in the investigated area is overexploited status and needs urgent management considerations.